2008
DOI: 10.1001/archopht.126.6.816
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Cell Damage by Free Radicals Associated With Ultrasound Oscillation

Abstract: To determine whether ultrasound oscillations in the anterior chamber cause corneal endothelial injury by free radicals.Methods: A phacoemulsification probe was introduced into the anterior chamber of rabbits' eyes through a limbal incision, and ultrasound oscillation was performed without emulsifying the lens. Rabbits were assigned to 4 treatment groups: (1) no treatment (controls); (2) only irrigation with a salt solution; (3) ultrasound only; and (4) ultrasound oscillations with a salt solution of 0.001M asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 31 publications
1
53
0
4
Order By: Relevance
“…52 Laboratory and animal studies have shown that ultrasound power within the anterior chamber causes oxidative stress and cellular injury, with the production of free radicals that are toxic to the corneal endothelium. 53,54 However, the magnitude of this cellular damage in vivo with modern phacoemulsification techniques is uncertain, so its clinical relevance remains unclear.…”
Section: Lens Liquefaction and Fragmentationmentioning
confidence: 99%
“…52 Laboratory and animal studies have shown that ultrasound power within the anterior chamber causes oxidative stress and cellular injury, with the production of free radicals that are toxic to the corneal endothelium. 53,54 However, the magnitude of this cellular damage in vivo with modern phacoemulsification techniques is uncertain, so its clinical relevance remains unclear.…”
Section: Lens Liquefaction and Fragmentationmentioning
confidence: 99%
“…Reports of corneal endothelial damage secondary to the use of ultrasound during phacoemulsification have been attributed to the release of free radicals due to cavitation. [131][132][133][134] However, the aqueous humor is rich in antioxidants, including ascorbic acid, and the lens has a coating of glutathione, another effective antioxidant. These endogenous antioxidants provide some endothelial protection.…”
mentioning
confidence: 99%
“…A szabadgyök-képződés az egyik legfontosabb, a szür-kehályog-műtét során kialakuló endothelsejt-károsodás-hoz vezető folyamat [11][12][13][14][15].…”
Section: Eredeti Közleményunclassified
“…Murano és munkatársainak vizsgálatai szerint az oxidatív stressz apoptózist indukálhat a cornealis endothelsejtekben. A szabad gyökök károsítják a plazmamembránok, a mitokondriumok, az endoplazmatikus reticulum és a sejtmagok membránrendszerét, illetve közvetlenül hatnak a DNS-transzkripcióra, amely hatások következtében sejtoedema és -necrosis alakulhat ki [11].…”
Section: Megbeszélésunclassified